Reduction of HbA1c and diabetes-related distress after intervention in a diabetes day care clinic in people with type 2 diabetes but not with type 1 diabetes - Kuniss, Nadine; Müller, Ulrich Alfons; Kloos, Christof; Wolf, Gunter; Kramer, Guido (Experimental and Clinical Endocrinology & Diabetes, 2018)
Objective The aim of this prospective, longitudinal study was to assess diabetes-related distress in people with diabetes mellitus type 1 (DM1) and type 2 (DM2) treated for diabetes-related problems and to evaluate, whether distress by diabetes are reduced after intervention in a diabetes day care clinic (DDC).Methods Diabetes-related burden was assessed with the “Problem Area In Diabetes” (PAID) questionnaire before (T0), directly after (T1) and 6 months after intervention (T2) in the DDC in 72 people (18 DM1, 54 DM2) admitted with a diabetes-specific problem to a DDC in a University department for metabolic diseases. A PAID score of ≥40 was considered as high diabetes-related distress.Results The PAID score in people with DM1 was not significantly different between T0, T1 and T2. Furthermore, neither HbA1c nor insulin dose did change at T2. In participants with DM2, the PAID score decreased significantly from T0 to T1 (18.4±15.9 vs. 15.4+± 13.0, p=0.042) and preserved the benefit at T2 (15.0±13.3). In addition, there was a significant reduction in HbA1c (−1.2%, p<0.001) and body weight (−1.3 kg, p=0.038) between T0 and T2. Insulin dose per day was 15.0 IU/day lower at T1 (p=0.006) and 9.0 IU/day lower at T2 (p=0.212) in comparison to T0.Conclusions Diabetes-related distress was reduced after a problem-oriented intervention in a DDC in people with DM2 but not with DM1. Although, all participants at tertiary care level had serious diabetes-specific problems before intervention, mean PAID score was far under the threshold of 40 points thus distress was low.
Keywords: diabetes day care clinic; diabetes-related distress; PAID questionnaire